‘DISPLACEMENT’, KRITERIA DEKONSTRUKSI PETER EISENMAN - Mubarrok, Noor Zakiy (Jurnal Arsitektur Komposisi, 2016)
Abstract: The implementation of deconstruction in architecture presents an extraordinary building, that no rarely lob the name of the designer, no exception for an American architect and theorists, Peter Eisenman. ‘Displacement’ is the notion of Peter Eisenman contains some criteria to implement deconstruction in architecture. The purpose of this research is to explore the thoughts and views of Peter Eisenman about deconstruction in architecture, especially about the notion of ‘displacement’, and its application in the design.Keywords: architecture deconstruction, displacement, peter eisenman Abstrak: Penerapan dekonstruksi dalam arsitektur, menghasilkan karya arsitektur yang luar biasa, yang tak jarang melambungkan nama perancangnya, tak terkecuali Peter Eisenman, seorang arsitek dan teoritikus kebangsaan Amerika. Displacement, merupakan ide yang dicetuskan Peter Eisenman berisi kriteria-kriteria yang harus dipenuhi sebagai upaya menerapkan dekonstruksi dalam arsitektur. Tujuan dari penelitian ini adalah untuk mengeksplorasi pemikiran serta pandangan Peter Eisenman tentang dekonstruksi dalam arsitektur terutama tentang ide Displacement, serta aplikasinya pada rancangan.Kata kunci: dekonstruksi dalam arsitektur, displacement, peter eisenman